The philosophy of education of the orthodox saints: historical and theological perspectives - Maillis, James (My University, 2006)
This thesis, presented as a curriculum, discusses the profound and inspiring educational example, which is given to the world by the Orthodox saints, who have completely submitted themselves to God, the Holy Trinity. The Orthodox saints and martyrs, unmatched in their God-inspired courage, wisdom and holiness of life, have taught and defended the unique, absolute truth that is Orthodox Christianity, without change and throughout history, for the good of all mankind. The discussion contrasts the cowardly subservience and relativism practiced, and consequently taught to the world, by many Orthodox ecumenists and others, with the great courage and holiness of life, in the face of immense danger and suffering, that is practiced, and consequently taught to humanity, by the Orthodox saints.
This file was last viewed in Adobe Reader 7.0.
Keywords: Christian saints; Christian education -- Curricula.; Orthodox Eastern Church